Раціональні режими роботи автобусів на маршрутах міського пасажирського транспорту - Кристопчук, Михайло; Карпан, Тетяна; Токарець, Сергій (Видавництво Львівської політехніки, 2015)
The article reveals the shortcomings of city passenger transport system and justifies the feasibility of implementing combined modes of the bus traffic on city routes.
Rational modes of bus operation on public transport routes